The Application of Learning Model (Google and Google Form) Based Android toward Students’ Activities and Research Methodology Learning Outcomes - Syamsuni HR; Hairuddin K; Elli Elli (Journal of Innovation in Educational and Cultural Research, 2022)
Technology is an instrument that has been affected in every line of life including learning process, one technology that can be utilized in the learning process namely an android smartphone. Android can be made to make easy for students in find theory of methodology research, can be used in evaluation of learning outcomes and others. This study aimed to know the effectiveness of learning models based android on activities and methodology research learning outcomes of students, to know Response Description of Student In using Learning Model based Android. Research design used a pretest-posttest-group with taking sample, used a random sampling of 250, the instrument used test about description and non test in the form of questionnaire response of students and analyzed with stats inferential namely T test. Research results show that t test on learning outcomes with obtained t-count = 4. 677 is bigger than t table = 1.66 reinforced with N-gain value of experimental class of 0.71 compared control class was equal to 0.54 then the average Mark experimental class was better compared with control class, the use of learning media based on android app has influence of 60.16% on learning outcomes and learning media based android app got positive response for student with results questionnaire of 80.05%.